PENENTUAN SUBJEK HUKUM DALAM PERTANGGUNGJAWABAN PIDANA ATAS PEMBERITAAN PENCEMARAN NAMA BAIK OLEH PERS - Wulandari, Arsem; Sambas, Nandang (LPPM STIH Awang Long, 2025)
Freedom of the press is an important foundation of democracy, but it is not without limits. There are legal limits that must be adhered to, especially regarding news that can defame a person's good name. This article discusses who can be held criminally responsible if the press reports defamation, based on Law Number 40 of 1999 concerning the Press. This study uses a normative-juridical method, namely by analyzing relevant laws, legal theories, and court decisions. The results show that the Press Law actually prioritizes dispute resolution through the Press Council. However, if this defamation case has met the elements of a crime, the responsible party is not only the journalist. This can also include the person in charge of the editorial office, the press company, and even other parties involved in the crime. To determine who is responsible, an in-depth analysis is needed of the roles and responsibilities of each party in the production and distribution of news.